1988
DOI: 10.7326/0003-4819-109-2-95
|View full text |Cite
|
Sign up to set email alerts
|

Prednisone Withdrawal Followed by Recombinant Alpha Interferon in the Treatment of Chronic Type B Hepatitis

Abstract: The immunologic priming provided by a short course of prednisone used with alpha interferon may be an effective treatment for selected patients with chronic type B hepatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
1

Year Published

1989
1989
2005
2005

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 171 publications
(42 citation statements)
references
References 19 publications
1
40
1
Order By: Relevance
“…[20][21][22][23][24][25][26][27][28][29] In addition, histological assessments of patients in other studies of lamivudine have shown that liver biopsy features improve significantly during lamivudine-induced suppression of HBV replication. 5,30,31 Further controlled trials of prolonged lamivudine treatment are in progress to define the efficacy and safety of lamivudine therapy and maintenance of virological responses after drug withdrawal.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23][24][25][26][27][28][29] In addition, histological assessments of patients in other studies of lamivudine have shown that liver biopsy features improve significantly during lamivudine-induced suppression of HBV replication. 5,30,31 Further controlled trials of prolonged lamivudine treatment are in progress to define the efficacy and safety of lamivudine therapy and maintenance of virological responses after drug withdrawal.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic trials with adenine arabinoside or interferon have shown these agents to be relatively ineffective, and their use has been accompanied by considerable toxicity (1,3,16,20,21). However, prednisone withdrawal followed by treatment with recombinant alpha interferon has shown more promise in the treatment of chronic type B hepatitis (13). We chose the primary hepatocyte culture of DHBV (19) to screen for antiviral agents effective against hepadnaviruses.…”
mentioning
confidence: 99%
“…Interferon has been used in a few cases, but is often prematurely withdrawn because of its hematologic toxicity. More importantly, it appears to lack efficacy in the prevention of HBV reactivation, especially in immunosuppressed patients [8,13,20,23,[34][35][36][37][38]. One of our patients, due to a lack to response to lamivudine, was given interferon, but he did not respond.…”
Section: Reactivation Of Hepatitis B In Patients With Chronicmentioning
confidence: 79%